Association of meeting the 24-h movement guidelines with high blood pressure in adolescents: a cross-sectional study - Christofaro, Diego G. D. [UNESP]; Ferrari, Gerson; Cucato, Gabriel G.; Mota, Jorge; Silva, Danilo R.; Vanderlei, Luiz Carlos M. [UNESP]; Tebar, William R. [UNESP]; Brazo-Sayavera, Javier (Springer Nature, 2024)
The 24-h movement guidelines for children and adolescents comprise recommendations for adequate sleep, moderate to vigorous physical activity (MVPA) and sedentary behaviour (SB). However, whether adolescents who meet these 24-h movement guidelines may be less likely to have high blood pressure (HBP) has not been established. The present study assessed the association between meeting 24-h movement guidelines and HBP in a school-based sample of 996 adolescents between 10–17 years (13.2 ± 2.4 years, 55.4% of girls). Blood pressure was measured using a digital oscillometric device, while sleep, MVPA and SB were measured using the Baecke questionnaire. The association between the 24-h movement guidelines and HBP was performed using binary logistic regression adjusted for sex, age, socioeconomic status, and body mass index. It was observed that less than 1% of the sample meet the three 24-h movement guidelines. The prevalence of HBP was lower in adolescents who meet all three movement 24-h guidelines (11.1%) compared to those who did not meet any guidelines (27.2%). Individual 24-h movement guidelines analysis showed that adolescents with adequate sleep were 35% less likely to have HBP (OR = 0.65; 95% CI 0.46–0.91). Meeting sleep guidelines combined with meeting MVPA (OR = 0.69; 95% CI 0.50–0.95) or SB (OR = 0.67; 95% CI 0.48–0.94) was inversely associated with HBP. Adolescents who meet two or three 24-h movement guidelines were respectively 47% (OR = 0.53; 95% CI 0.29–0.98) and 34% (OR = 0.66; 95% CI 0.48–0.91) less likely to have HBP. In adolescents, meeting sleep and 24-h movement guidelines were inversely associated with HBP.
Keywords: Cardiovascular parameters; Movement guidelines; Physical activity; Sedentary behaviour; Sleep